The gravitational potential energy regeneration system with closed-circuit of boom of hydraulic excavator. (1st January 2017) - Chen, Mingdong; Zhao, Dingxuan
Abstract: Considering the disadvantage of higher throttling loss for the open-circuit hydrostatic transmission at present, a novel gravitational potential energy regeneration system (GPERS) of the boom of hydraulic excavator, namely the closed-circuit GPERS, is proposed in this paper. The closed-circuit GPERS is based on a closed-circuit hydrostatic transmission and adopts a hydraulic accumulator as main energy storage element fabricated in novel configuration to recover the entire gravitational potential energy of the boom of hydraulic excavator. The matching parameter and control system design are carried out for the proposed system, and the system is modeled based on its physical attributes. Simulation and experiments are performed to validate the employed mathematical models, and then, the velocity and the pressure performance of system are analyzed. It is observed that the closed-circuit GPERS shows better velocity control of the boom and response characteristics. After that, the average working efficiency of the closed-circuit GPERS of boom is estimated under different load conditions. The results indicate that the proposed system is highly effective and that the average working efficiency in different load conditions varied from 60% to 68.2% for the experiment platform. Highlights: A novel closed-circuit energy regeneration system of the boom is proposed. The mathematical models are established and control system is designed. The control performance of system is analyzed by simulations and experiments. The efficiency of the system in different load conditions varies from 60% to 68.2%.